أثر التمويل المصرفي الإسلامي على النمو الاقتصادي في ماليزيا، دراسة قياسية خلال الفترة (2000-2021) - منير, بن عيسى; سمية, موري (جامعة الوادي university of eloued, 2023)
تهدف هذه الدراسة إلى أهمية التمويل المصرفي الإسلامي ودوره في تمويل مختلف القطاعات الاقتصادية في ماليزيا، وكذا تحليل أثر التمويل المصرفي الإسلامي على النمو الاقتصادي للبلد للفترة 2000-2021، باستخدام نموذج الانحدار الخطي البسيط، وهذا بالاعتماد على النمو الاقتصادي كمتغير تابع واجمالي التمويل المصرفي الإسلامي كمتغير تفسيري. وخلصت الدراسة إلى أن للتمويل المصرفي الإسلامي له أثر إيجابي ومعنوي على النمو الاقتصادي، وأن للتمويل المصرفي الإسلامي أهمية في تفسير النمو الاقتصادي في الاقتصاد الماليزي. This study aims at the importance of Islamic banking financing and its role in financing various economic sectors in Malaysia, as well as analyzing the impact of Islamic banking financing on the economic growth of the country for the period 2000-2021, using the simple linear regression model, and this is based on economic growth as a dependent variable and total Islamic banking financing as a variable interpretative. The study concluded that Islamic banking finance has a positive and significant impact on economic growth, and that Islamic banking finance is important in explaining economic growth in the Malaysian economy
مقال
Keywords: تمويل مصرفي ; تمويل إسلامي ; نمو اقتصادي ; اقتصاد ماليزي